DEVELOPMENT OF POLYMER BLEND MEMBRANE FOR GAS SEPARATION - ABDUL MANNAN, HAFIZ (2014)
The main objective of this work is to study the effect of solvents and polymer blending on the development of polymeric blend membrane (PBM). Polysulfone (PSU) and polyethersulfone (PES) were selected as glassy polymers and polyvinyl acetate (PVAc) was chosen as rubbery polymer. Pure polymeric membranes were prepared in N-Methyl-2-pyrrolidone (NMP) and N, N-Dimethylformamide (DMF) solvents in order to evaluate the effect of casting solvent. The glassy/rubbery polymer blend membranes were prepared by blending PSU-PVAc and PES-PVAc while the glassy/glassy polymer blend membranes were prepared by blending PSU-PES. The prepared pure and PBM membranes were characterized in terms of morphology, miscibility, chemical bonding and thermal stability and tested for permeation of carbon dioxide and methane gases.